A case of polycystic ovary syndrome with inevitable miscarriage and multi-site venous thrombosis caused by hereditary protein C deficiency - Minglin Zhong; Yanping Tu; Xiuhong Peng; Yue Song; Jiahe Zhou; Xiaowei Zhang; Qiuyi Xu; Li Li (Gynecological Endocrinology, 2022)
Background Polycystic ovarian syndrome (PCOS) affects up to 18% of reproductive-aged women and raises the risk of venous thromboembolic disease (VTE), due to metabolic features and an apparent fibrinolytic state. Recent studies have shown an increased risk of VTE (1.5- to 2-fold) in patients with PCOS as compared to those without PCOS. Mutations in the Protein C (PC) gene (PROC) lead to deficiency or dysfunction of the protein, Protein C deficiency is the main clotting physiological inhibitor of protein C cofactors, and is a risk factor for venous thrombosis, which can cause a variety of events, including miscarriage. This case report proposes a correlation between PCOS, protein C deficiency, venous thrombosis and inevitable miscarriage.Case presentation A 33-year-old Chinese woman was diagnosed with Polycystic Ovary Syndrome (PCOS) in 2015. During the course of treatment, she took ethinylestradiol and cyproterone acetate tablets for more than one year. In 2016, she was sent to a hospital for emergency care due to explosive thrombosis (thrombosis in multiple parts of the body and pulmonary thrombosis). In 2020, the patient became pregnant via natural means and came to our hospital for treatment. During the second trimester, she experienced an inevitable miscarriage. High-throughput sequencing (NGS) of peripheral blood lymphocytes revealed that the patient had a protein C deficiency resulting from a heterozygous mutation deletion of 572_574 in exon 7.Conclusion PC deficiency in conjunction with PCOS and the concomitant use of oral contraceptive (COC) would increase the risk of VTE, especially in the early stages of COC use.